Ecopsychology, phenomenology, and the environment : the experience of nature - Castrillon, Fernando; Vakoch, Douglas A. (Springer New York, 2014)
A significant step in the evolution of ecopsychology has been the field's growing awareness of its long-standing affinity with phenomenology. Now, at a time when the natural world is viewed as somewhere between threatening, threatened, and invisible, an examination of the often implicit bond between these two spheres of inquiry makes increasing sense.  Ecopsychology, Phenomenology, and the Environment: The Experience of Nature explores the intersection of the two disciplines through a diverse group of ecological thinkers. Emphasizing the directly felt experience of the wild as opposed to overtly scientific approaches, this evocative volume presents fresh perspectives on the intimacy of nature, environmentally-related morals and ethics, and the realities engendered by climate change. With profound vision and lyrical elegance, contributors reveal the transformative power of the natural world and its expansive effects on our senses and consciousness. And perhaps most notably, these chapters challenge us as humans to revise how we understand ourselves in relation to the rest of nature.  Included in the coverage: The naturalist's presence: toward a relational phenomenology of attention and meaning. Aliveness and transformation in wilderness. Apocalyptic imagination and the silence of the elements. The who of environmental ethics: phenomenology and the moral self. Climate chaos, ecopsychology, and the maturing human being. Unhumanizing phenomenology to decode the language of Earth. Ecopsychology, Phenomenology, and the Environment: The Experience of Nature will find an engaged audience among ecopsychologists, environmental and conservation psychologists, and other psychologists and psychotherapists interested in environmental issues, as well as phenomenological psychologists. It will also appeal to environmental researchers working with psychological or phenomenological perspectives and philosophers concerned with environmental issues and ethics.